ARUS KAS, LABA, DAN LEVERAGE PADA FINANCIAL DISTRESS PERUSAHAAN NON BANK - Mishelei Loen; Euis Nessia Putri; Imam Nurcahyo Fambudi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to determine cash flow, profit and leverage on financial distress for non-bank companies listed on the Indonesia Stock Exchange (IDX) for the period 2021 to 2023. This research uses quantitative methods, the type of data used is secondary data. The population in this study were all non-bank companies listed in IDX (Indonesia Stock Exchange) for the period 2021-2023, a total of 30 samples. Sampling in this study using purposive sampling technique. The results of this research and it can be concluded that cash flow, profit and leverage have a significant effect on financial distress. The implications of this research for companies experiencing financial distress conditions should be able to maintain financial conditions and be more careful in making decisions in dealing with financial distress conditions. As for investors, it is hoped that it can provide an overview to be wiser in deciding to invest in a company by paying attention to the company's financial condition and performance and other factors so that the investment becomes more appropriate and produces the desired profit, and to be more cautious in buying stocks or bonds issued by a company that has been identified as likely to experience financial distress.